Recurrent pneumonitis in a 10-year-old girl with pigeon breeder's disease - Dilber, Embiya; Özçelik, Uğur; Göçmen, Ayhan; Mısırlıgil, Zeynep; Kiper, Nural (The Turkish Journal of Pediatrics, 1997)
Hypersensitivity pneumonitis is an allergic disease resulting from sensitization to inhaled organic dust, usually manifest with recurrent bouts of cough, dyspnea and fever. Most of the reported cases concern the adult population. The disease is rarely seen in the pediatric age group, as stated by most of the reviews on the subject. In this article, a case with hypersensitivity pneumonitis is described. Precipitating antibodies to avian protein were demonstrated in serum from a girl with recurrent bouts of pneumonitis which was otherwise unexplained.
Keywords: hypersensitivity pneumonitis; pigeon breeder's disease; precipitating antibodies